Precision mass measurements of magnesium isotopes and implications for the validity of the isobaric mass multiplet equation - Brodeur, Maxime; Drozdowski, Oliver (Physical review, 2017)
If the mass excess of neutron-deficient nuclei and their neutron-rich mirror partners are both known, it can be shown that deviations of the isobaric mass multiplet equation (IMME) in the form of a cubic term can be probed. Such a cubic term was probed by using the atomic mass of neutron-rich magnesium isotopes measured using the TITAN Penning trap and the recently measured proton-separation energies of 29Cl and 30Ar. The atomic mass of 27Mg was found to be within 1.6σ of the value stated in the Atomic Mass Evaluation. The atomic masses of 28,29Mg were measured to be both within 1σ, while being 7 and 33 times more precise, respectively. Using the 29Mg mass excess and previous measurements of 29Cl, we uncovered a cubic coefficient of d=28(7)keV, which is the largest known cubic coefficient of the IMME. This departure, however, could also be caused by experimental data with unknown systematic errors. Hence there is a need to confirm the mass excess of 28S and the one-neutron separation energy of 29Cl, which have both come from a single measurement. Finally, our results were compared with ab initio calculations from the valence-space in-medium similarity renormalization group, resulting in a good agreement.